2021
DOI: 10.1002/ctm2.410
|View full text |Cite
|
Sign up to set email alerts
|

Rebalancing TGF‐β/Smad7 signaling via Compound kushen injection in hepatic stellate cells protects against liver fibrosis and hepatocarcinogenesis

Abstract: 1. CKI -suppresses liver fibrosis and hepatocarcinogenesis in both preclinical and clinical studies. 2. CKI inhibits HSCs activation by stabilizing the interaction of Smad7/TGFβR1 to rebalance Smad2/Smad3 signaling, acting as an alternative approach to target TGF-β signaling.3. High expression of Smad7 and low expression of TGFβR1 in HCC tumors and surrounding normal liver tissues can be tumor suppressive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 51 publications
2
19
0
Order By: Relevance
“…Transforming growth factor−β1 (TGF−β1) is believed to be the most potent fibrogenic cytokine, stimulating HSCs activation (Tsukamoto et al, 2011;Chen et al, 2021). It is reported that strategies targeting at disrupting TGF−β1 synthesis and/or signaling pathways markedly reduce liver fibrosis (Li et al, 2021;Sun et al, 2021;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Transforming growth factor−β1 (TGF−β1) is believed to be the most potent fibrogenic cytokine, stimulating HSCs activation (Tsukamoto et al, 2011;Chen et al, 2021). It is reported that strategies targeting at disrupting TGF−β1 synthesis and/or signaling pathways markedly reduce liver fibrosis (Li et al, 2021;Sun et al, 2021;Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…39 Upon hepatocellular injury, nonparenchymal cells, especially Kupffer cells, secrete proinflammatory/profibrogenic factors that rapidly attack and activate the HSCs and eventually lead to liver fibrosis. 40 HSCs are the predominant pathogenic cells that are responsible for the overproduction of fibrillar collagens in liver fibrosis. Therefore, substantial efforts that target HSCs have been made for the treatment of liver fibrosis that show promising results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Smad7 was identified as a key target of CKI in the treatment of liver fibrosis. CKI up-regulated Smad7, inhibited TNF-βR1, and suppressed TNF-β/Smad signaling pathway to prevent the development of chronic liver fibrosis and HCC ( 62 ). NHE-06 exerted a strong anti-inflammatory activity on HCC through the suppression of NF-κB/IL-6/STAT3 signaling and TGF-α and PTSG2.…”
Section: The Immunoregulatory Patterns Of Chinese Medicine Compounds In Cancer Therapymentioning
confidence: 99%